2017
DOI: 10.3389/fmicb.2017.00063
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Molecular Epidemiology of ESBL-Producing Escherichia coli Isolated from Outpatients in Town Hospitals of Shandong Province, China

Abstract: This study aimed to investigate antimicrobial resistance and molecular epidemiology of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli (E. coli) isolated from outpatients in town hospitals of Shandong province, China. Antimicrobial susceptibility of ESBL-producing E. coli was tested using the disk diffusion and resistance genes encoding for β-lactamases (blaTEM, blaCTXM, and blaSHV) were detected by polymerase chain reaction (PCR). Multilocus sequence typing (ST) of ESBL-producing E. coli was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 45 publications
(59 reference statements)
1
20
1
Order By: Relevance
“…Four authors provided the required data and resulted in inclusion of these reports. One author confirmed that no pregnant women were studied in their report . One author confirmed that pregnant women were not investigated .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Four authors provided the required data and resulted in inclusion of these reports. One author confirmed that no pregnant women were studied in their report . One author confirmed that pregnant women were not investigated .…”
Section: Resultsmentioning
confidence: 83%
“…One author confirmed that no pregnant women were studied in their report. 48 One author confirmed that pregnant women were not investigated. 49 Two authors noted that only the laboratory data were collected in their studies and clinical information (whether asymptomatic carriage or clinically significant UTI) were not documented.…”
Section: Esbl-producing Enterobacteriaceaementioning
confidence: 99%
“…UTI is the second most prevalent bacterial infection in the community, and uropathogenic E. coli accounts for 70-95% of community-acquired UTI cases [4][5][6]. β-Lactam antibiotics due to their broad antibacterial spectrum and minimal side effects are widely used in the treatment of various infections such as UTI [7]. Interestingly, the non-rational and intensive use of antibiotics by humans and animals is considered as one of the mechanisms that can accelerate the process by which bacteria can acquire resistance [8].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, bla CTX−M has rapidly increased and is now widely found in clinically isolated E. coli across the world. 8 ESBLs, especially of the CTX-M type, are strongly associated with specific clonal E. coli strains. 9 To date, little is known about the epidemiology of ESBL variants in Thailand.…”
Section: Introductionmentioning
confidence: 99%